Evaluación del tratamiento biológico para la disminución de azufre y metales pesados en aceites lubricantes usados de motor diésel, como posible alternativa para la industria automotriz (2019)
The Used Oil of Diesel engine contains compounds of phosphorus, silicon, iron, calcium, magnesium, zinc, sodium and water, which comes mainly from the oxidation and wear of metal parts of the engine, combustion incomplete and degradation of additives. The illegal release of used oil to the environment causes a significant environmental impact over hidric, air and soil resources. The present investigation focused on proposing and evaluating a biological treatment at laboratory level, which will allow the remotion of sulfur and heavy metals present in the Used Oils generated by SENA (Transport Technologies Center) using sulfate-reducing bacteria. The qualitative and quantitative evaluation of the removal of sulfur and heavy metals was performed for 29 days, finding that the native strains of sulfate-reducing bacteria are suitable for the proposed aim, due they carry out the metabolic of sulfates dissimilatory reduction pathway. The proposed biological treatment reached average removal percentages upper than 70% in iron, silicon, aluminum and copper contaminants; furthermore, the sulfur compounds present in the used oil matrix were completely removed.